Reading comprehension in incoming university students (Docentes 2.0 Journal, 2024)
Reading comprehension refers to the ability to understand, use, reflect, and show interest in written texts to achieve personal goals, foster individual knowledge development, and actively participate in society. Therefore, reading becomes a fundamental skill for learning in all disciplines of knowledge. In this context, this study aimed to determine the reading comprehension level of incoming university students. The research was based on the deductive method and positivist paradigm, with a quantitative approach, descriptive design, and cross-sectional type. The study sample consisted of 95 male and female students. The instrument corresponds to a written test comprising five texts with five questions each. Descriptive statistics were used for data processing. The results reveal that most incoming university students have a high level of literal reading comprehension, while in inferential and criterion comprehension, the majority are at the middle level; this means that leveling courses or free credits should be implemented within the university curricular programs that allow incoming students to improve their reading competence. Understanding this skill is of utmost importance since reading is the main medium through which new knowledge is acquired in university education, both in disciplinary and general terms. It is concluded that most incoming university students reach an average level in this capacity.
Keywords: Reading competence; reading comprehension; communicative competences; university students